Multispecialty comparison of point-of-care-ultrasound use, training, and barriers: a national survey of VA medical centers - Dana M. Resop; Brian Bales; Rebecca G. Theophanous; Jessica Koehler; Jeremy S. Boyd; Michael J. Mader; Jason P. Williams; Robert Nathanson; Zahir Basrai; Elizabeth K. Haro; Rahul Khosla; Erin Wetherbee; et al. (The Ultrasound Journal)
Abstract Background As more specialties have begun to use Point-of-Care Ultrasound (POCUS) in patient care, hospitals and healthcare systems have been investing increasing resources in POCUS infrastructure (training, equipment, and administration). Since each specialty uses different POCUS applications, healthcare systems seek to identify commonalities and differences between specialties to make thoughtful investments in POCUS infrastructure to support each specialty’s use of POCUS while minimizing redundancies. Historically, past studies have focused on POCUS use in individual specialties, primarily emergency medicine and critical care, but comparative studies of different specialties are needed to guide investment in POCUS infrastructure and bolster POCUS implementation across healthcare systems. We conducted a cross-sectional survey of all Veterans Affairs (VA) medical centers in the United States and compared data from 5 different specialties on current usage, training needs, and barriers to POCUS implementation. Results Data were collected from facility chiefs of staff (n = 130; 100% response rate) and chiefs of emergency medicine (n = 101; 92% response rate), critical care (n = 93; 83% response rate), hospital medicine (n = 105; 90% response rate), anesthesiology (n = 96; 77% response rate), and surgery (n = 104; 95% response rate). All specialties surveyed reported current POCUS use (surgery 54%, hospital medicine 64%, anesthesiology 83%, emergency medicine 90%, and critical care 93%) but more importantly, a greater desire for training was seen. Procedural POCUS applications were most often used by all specialties, despite decreased procedural POCUS use since 2015 for all specialties except critical care. Diagnostic POCUS use generally increased from 2015 to 2020, although use of specific POCUS applications varied significantly between specialties. Barriers limiting POCUS use included lack of training (53–80%), access to ultrasound equipment (25–57%), and POCUS infrastructure (36–65%). Conclusions From 2015 to 2020, POCUS use increased significantly in emergency medicine, critical care, internal medicine, anesthesiology, and surgery, although use of specific applications varied significantly between specialties. Lack of training and POCUS infrastructure were common barriers to POCUS use across specialties. Desire for training exceeded current use for several POCUS applications. These findings can guide implementation and standardization of  POCUS use  in hospitals and healthcare systems.